2018
DOI: 10.2196/preprints.10321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobile App for Improved Self-Management of Type 2 Diabetes: Multicenter Pragmatic Randomized Controlled Trial (Preprint)

Abstract: Background: A growing number of mobile apps are available to support self-management of diabetes. One such app, called BlueStar™, has been shown to significantly reduce glycemic control in small trials. While the efficacy of the app led to become the first app in the USA to receive FDA approval as a Mobile Prescription Therapy, its effectiveness across a range of usual care settings remains unclear.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Related studies have shown that both apps resulted in significant improvement in HbA1c control compared with the HbA1c of the control group [11][12][13] . However, studies on Diabetes Pal and BlueStar, two other apps, showed no HbA1c reduction 14,15 . To date, most of the studies have been single-centre trials with small sample sizes and have mainly focused on glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have shown that both apps resulted in significant improvement in HbA1c control compared with the HbA1c of the control group [11][12][13] . However, studies on Diabetes Pal and BlueStar, two other apps, showed no HbA1c reduction 14,15 . To date, most of the studies have been single-centre trials with small sample sizes and have mainly focused on glycaemic control.…”
Section: Introductionmentioning
confidence: 99%